PENGARUH IMPLEMENTASI MEDIA INTERAKTIF BERBASIS WORDWALL TERHADAP PEMAHAMAN UNDAK USUK BAHASA SUNDA DI SD - Salsyabilla Aurorra Hanadrie; Dewi Aila; Muhammad Rijal Wahid Muharram (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This text addresses the challenge of preserving Indonesia's regional languages, specifically the Sundanese language, which is losing its appeal among younger generations. This lack of interest is primarily due to monotonous, conventional teaching methods, as observed at SDN Pangandaran, where teachers only use textbooks. To combat this disengagement and reignite student enthusiasm, the text proposes integrating technology into education. Interactive learning media, such as Wordwall, are identified as a potential solution to help educators deliver material in a more engaging way that is relevant to the current digital era. Therefore, this research aims to examine how the use of Wordwall-based interactive media can increase student interest and understanding of the Sundanese language, especially concerning undak usuk basa Sunda (levels of language in Sundanese).